2012
DOI: 10.1136/emermed-2012-201124
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for 48-hours mortality after prehospital treatment of opioid overdose

Abstract: The author found a 48-hours mortality of 8.4%. Advanced age and opioid overdose in the weekends were significant risk factors. Release on scene after treatment was associated with a very small risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…Hickman and colleagues showed that overdose during weekends was associated with an odds ratio of 1.48 for mortality in methadone overdose . In another study, it was shown by logistic regression analysis that age over 50 and overdose during weekends were associated with opioid overdose‐related 48‐hr mortality . We did not assess overdose during weekends, but by linear regression analysis, increased age was shown to be a predictor of hospital stay in our study.…”
Section: Discussioncontrasting
confidence: 48%
“…Hickman and colleagues showed that overdose during weekends was associated with an odds ratio of 1.48 for mortality in methadone overdose . In another study, it was shown by logistic regression analysis that age over 50 and overdose during weekends were associated with opioid overdose‐related 48‐hr mortality . We did not assess overdose during weekends, but by linear regression analysis, increased age was shown to be a predictor of hospital stay in our study.…”
Section: Discussioncontrasting
confidence: 48%
“…These findings agree with previous studies evaluating outpatient opioid OD risk factors. Specifically, a study by Wichmann and colleagues found that patients who present to the emergency room with an opioid OD are more likely to die from the OD if they are older 14 . Other studies have found that patients with higher socioeconomic status (measured in education level), female gender, mood disorders and those taking sedating medications have an increased risk of opioid OD outside the hospital 15, 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of death was overdose. Previous studies have found that rebound toxicity and death in the immediate days after an overdose attendance are rare among those who are left on the scene by ambulance services after naloxone treatment . This could suggest that an individual survives the first few days after an overdose attendance, but thereafter there is an increased risk of death, in particular from a new overdose.…”
Section: Discussionmentioning
confidence: 99%
“…One of these risk factors is injecting drug use, which not only increases the risk of death from overdose, but also increases the risk of death from cutaneous injection‐related infections, venous disease and blood‐borne infections such as hepatitis and HIV . Other factors that are well known to be associated with higher mortality rates include non‐fatal overdoses, older age, being male, having a long injecting career and combining opioid injections with alcohol and/or benzodiazepines . In addition, there is an increased risk of fatal overdoses among opioid users in the first month after prison release or discharge from abstinence‐orientated drug addiction treatment .…”
Section: Introductionmentioning
confidence: 99%